(untitled) (Journal of Pharma Insights and Research, 2025)
Clonal hematopoiesis (CH) serves as a molecular connection between aging and pathological conditions, particularly cardiovascular diseases and hematologic malignancies. Recent progress in genetic sequencing have identified somatic mutations in genes such as TET2, DNMT3A, and JAK2 that drive clonal expansion of hematopoietic stem cells, leading to various systemic effects. These mutations, often termed clonal hematopoiesis of indeterminate potential (CHIP), occur in approximately 10-20% of individuals over 70 years old and significantly impact cardiovascular health through enhanced inflammation and atherosclerosis. Additionally, CHIP mutations serve as precursors to hematologic malignancies, with annual progression rates of 1-2% to conditions such as acute myeloid leukemia and myelodysplastic syndromes. Large cohort studies and animal models have demonstrated that specific mutations in epigenetic regulators and signaling molecules contribute to both cardiovascular pathology and malignant transformation. The relationship between aging, CHIP mutations, and disease progression presents opportunities for novel therapeutic techniques, including targeted anti-inflammatory strategies and epigenetic modulators. These findings have significant implications for risk stratification and early intervention in aging populations, potentially revolutionizing preventive medicine approaches for age-related diseases. Integration of CH screening into clinical practice may enable personalized risk assessment and guide therapeutic decisions, though challenges remain in standardizing detection methods and determining optimal intervention techniques